2010
DOI: 10.1258/hsmr.2009.009014
|View full text |Cite
|
Sign up to set email alerts
|

Major incident planning in primary care trusts in north-west England: a cross-sectional survey

Abstract: The Civil Contingencies Act (2004) requires UK primary care trusts (PCTs) to plan and respond to major health incidents. We carried out a cross-sectional survey of all PCTs in the north-west region of England using a telephone interview with a structured questionnaire. We assessed: (1) staff members responsible for emergency planning; (2) risk assessment; (3) training and exercises; and (4) the planned response to a major incident. Response rate was 61% (20/33). Twelve out of 20 employed an emergency planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
(5 reference statements)
2
7
0
Order By: Relevance
“…The U.K. research studies (Anathallee et al , 2007; Williams et al , 2007; Fell, 2008; Day et al , 2010) typically indicate shortfalls in the emergency preparedness of health-care services. Training and exercises are a major component of developing preparedness, but knowledge is lacking regarding their effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…The U.K. research studies (Anathallee et al , 2007; Williams et al , 2007; Fell, 2008; Day et al , 2010) typically indicate shortfalls in the emergency preparedness of health-care services. Training and exercises are a major component of developing preparedness, but knowledge is lacking regarding their effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…The application of the evidence-base is also reported to be patchy [3-5], and decision-making tends to be dependent on the individual and organisational culture of the agencies involved [13]. This was clearly exemplified by the current approach of emergency planning practitioners tending to “muddle through” situations, often relying on their previous experience and intuition, rather than any robust evidence base or understanding of the wider socio-political or behavioural aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, this work was conducted in the background but the horrifying terrorist attacks of 11 September 2001 and 7 July 2005 have catapulted the emergency management field up the political agenda [2]. Since then, research and publications in this field have accelerated, as demonstrated by the US experience following 11 September 2011 where in the past decade nearly seven hundred articles were published pertaining to this single event alone [3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacity assessment and capacity-building [26][27][28][29][30][31]: A study in this theme reports that surveys at the local health department level can provide information to guide development of capacity [31]. Evaluative information that relates to emergency preparedness and response can inform a deeper understanding of the capabilities important to preparedness [27].…”
Section: Identification Of Themes Phasementioning
confidence: 99%